Las medidas de protección contra el maltrato de la niñez y adolescencia en el marco del respeto a sus derechos y garantías constitucionales - Esquivel Madrid, Edgar Almilcar (2013)
This thesis, with the theme " Protection measures against abuse of children and adolescents in the context of respect for their rights and Constitutional guarantees," the different chapters describe relevant aspects of the topic under investigation. In the introduction, a summary of the mistreatment of children and adolescents, problematization is the reality of the lack of protective measures by the State to abused children focuses on the general and specific objectives stated , the hypothesis, the independent and dependent variables and resources are detailed. The theoretical framework is based, the Doctrinal part Jurisprudencial, Legislation regarding the object of study, it also presents comparative law referring to different laws about the mistreatment of children and adolescents is. In the methodology , the methods used are determined , the techniques applied in the field , such as direct observation, surveys the application of the citizens of Canton Quevedo, and interviews with such results tabulation was performed , analysis and data processing , reporting research and hypothesis testing was developed. The proposed legal reform to art. 217 paragraph 6 of the Code for Children and Adolescents , prevent child abuse. Finally conclusions and recommendations are detailed